The Cuesta de Rahue Basement Inlier (Southern Neuquén Precordillera, Argentina): A Devonian to Triassic polyphase orogenic record in northern Patagonia - Oriolo, Sebastián (2023)
New geological, structural, microstructural, and K-Ar biotite and illite geochronological data of igneous-metamorphic rocks exposed in the Cuesta de Rahue Basement Inlier are presented to reconstruct the Late Palaeozoic to Mesozoic tectonometamorphic and magmatic history of northwestern Patagonia. This block comprises a medium-grade metasedimentary sequence (Cuesta de Rahue Metamorphic Complex), Late Carboniferous granitoids and a low-grade metavolcano-sedimentary unit (Arroyo Coloco Metamorphic Complex). The Cuesta de Rahue Metamorphic Complex was deposited during the middle Palaeozoic and underwent Devonian low-pressure regional metamorphism, succeeded by the intrusion of granitoids at ca. 300 Ma. On the other hand, the Arroyo Coloco Metamorphic Complex record deformation and metamorphism at epizonal conditions (> 300 °C), constrained at ca. 232-199 Ma by K-Ar and XRD illite data. The Cuesta de Rahue Basement Inlier thus records a protracted orogenic evolution, recording Devonian metamorphism, Late Carboniferous-Permian Gondwanide tectonomagmatic processes, and Late Triassic deformation and metamorphism. Afterwards, this block was also affected by Mesozoic normal faulting and, finally, by Miocene-Pliocene Andean deformation. The latter was intimately related to reactivation of inherited basement fabrics, favouring a transpressional deformation regime.